Psychometric Properties of Interpersonal Communication skills Questionnaire (ISAQ) from the Viewpoint of Students at Tabriz University and Tabriz University of Medical Sciences - Firoz Mahmoodi; Zahra Samadi; Zeinab Fizolahzadeh (Zanjan University of Medical Sciences and Health Services, 2017)
Background and Objective: One of the skills needed for social life is interpersonal communication skills. Assessing the Interpersonal communication skills due to the growth and development of social networks is very important. This study aimed to validate the Fetro's (2000) interpersonal communication skills questionnaire among students of Tabriz University and Tabriz University of Medical Sciences. Materials and Methods: In this descriptivestudy, 750 students of Tabriz University and Tabriz University of Medical Sciences were selected by simple random sampling. Data collected by Fetro (2000) interpersonal communication skills questionnaire. This questionnaire has 65 items with five degrees based on Likert scale. Data were analyzed using Exploratory Factor Analysis through SPSS 23. Results: In total 750 Students filled questionnaires. 423 from University of Tabriz and 327 from of Tabriz University of Medical Sciences. Based on the results of exploratory factor analysis on original 65 items, 6 factors extracted and 54 items remained. Based on original questionnaire factors and literature extracted factors were labeled. So 45.26% of total variance were explained by these six factors (empathy and intimacy, communication skills, ability to maintain communication, assertiveness, listening and conflict resolution skills). Conclusion: According to the result of factor analysis, new validated questionnaire has less items and more components than the original questionnaire. So it is a suitable instrument for measuring interpersonal communication skills by researchers.